Plant genetic engineering, climate change and food security - Ortíz, R.; Jarvis, Andy; Fox, P; Aggarwal, Pramod K.; Campbell, Bruce M. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
This paper explores whether crop genetic engineering can contribute to addressing food security, as well as enhancing human nutrition and farming under a changing climate. The review is based on peer-refereed literature, using results to determine the potential of this gene technology. It also provides a brief summary of issues surrounding this genetic enhancement approach to plant breeding, and the impacts on farming, livelihoods, and the environment achieved so far. The genetic engineering pipeline looks promising, particularly for adapting more nutritious, input-efficient crops in the development of the world’s farming systems.